Pengaruh Bauran Pemasaran (Marketing Mix) Terhadap Minat Beli Pelanggan di Petromart Gresik - Damanik, Wina Yurika; Amir, Indra Tjahaja; Setiawan, Risqi Firdaus (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The purpose of this study is to analyze the effect of marketing mix that are product (X1), price (X2), place (X3), promotion (X4), people (X5), process (X6), and physical evidence (X7) towards costumer’s interest in buying (Y) at Petromart Gresik. Sample is determined with purposive sampling method and 50 Petromart Gresik’s customers are used as respondents. The analysis method in this study is Structural Equation Modelling - Partial Least Square (SEM-PLS). The result shows that product (X1), price (X2), place (X3), process (X6), and physical evidence (X7) have positive and significant effect on consumers’ interest in buying, but promotion (X4) and people (X5) do not have significant effect on consumers’ interest of buying at Petromart Gresik